2002
DOI: 10.1046/j.1365-2699.2002.00726.x
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual framework for studying species composition in fragments, islands and other patchy ecosystems

Abstract: Aim I propose and develop a new classification system to explain diversity patterns in habitat fragments, equally applicable to islands and other inherently patchy ecosystems. My primary goal is to provide an inclusive model to improve the comparability of studies and enhance future efforts to synthesize their findings, yielding a generalized basis for understanding species composition in patchy ecosystems. Results Differentiating islands from fragments and incorporating patch age and patch: matrix contrast, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
123
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(135 citation statements)
references
References 102 publications
3
123
0
4
Order By: Relevance
“…Local genetic and species diversity showed parallel patterns in this island-like system of outcrops in the Carpathian Mountains, which is an expected result in isolated mainland ecosystems (Michelangeli, 2000;Watson, 2002;Vellend, 2003;but see Puş caş et al, 2008;Sei et al, 2009). It also appears that the intra-and interspecific diversity patterns are shaped by similar mechanisms.…”
Section: Local Diversity Of Genes and Speciesmentioning
confidence: 55%
See 2 more Smart Citations
“…Local genetic and species diversity showed parallel patterns in this island-like system of outcrops in the Carpathian Mountains, which is an expected result in isolated mainland ecosystems (Michelangeli, 2000;Watson, 2002;Vellend, 2003;but see Puş caş et al, 2008;Sei et al, 2009). It also appears that the intra-and interspecific diversity patterns are shaped by similar mechanisms.…”
Section: Local Diversity Of Genes and Speciesmentioning
confidence: 55%
“…Although there is accumulating theoretical and empirical support for similarity between oceanic and mainland island systems (Vellend, 2003;Vellend and Geber, 2005;Wehenkel et al, 2006;Sei et al, 2009;Lamy et al, 2013), nonsignificant (Puş caş et al, 2008;Taberlet et al, 2012) and negative (Silvertown et al, 2009;Fady and Conord, 2010) correlations have also been reported. An important source of these contradictory results is the lack of a clear outline of the history of fragmentation and extent of habitat isolation, despite readily available frameworks (Watson, 2002). The older the fragmentation and the more pronounced the ecological contrast with the landscape matrix, the more likely the mainland habitat patches are to follow biogeographical processes typical of isolated oceanic island systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several frameworks have previously been developed for conceptualizing the structural composition of landscapes (Fischer, Lindenmayer, & Fazey, 2004;Forman, 1995;McIntyre & Barrett, 1992;Watson, 2002;Wiens, Stenseth, Van Horne, & Ims, 1993). However, these frameworks were not extended to classify the mechanisms driving isolation effects on animal populations.…”
Section: Limited Resource Accessmentioning
confidence: 99%
“…However, the relative importance of these factors in determining species distribution throughout the fragmented habitat differs among taxa, depending on life history traits such as dispersal ability (birds vs. reptiles) and level of dependence on the forest resources (specialists vs. generalists) (Ricklefs and Lovette 1999;Gascon et al 1999;Watson 2002). Moreover, historical factors (e.g.…”
Section: Introductionmentioning
confidence: 99%